Ріст пагонів та пошкодження листків Catalpa bignonioides Walt. в умовах техногенного навантаження - Leppik, M.V.; Bessonova, V.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
The influence of industrials ingredients contamination on growth and morphologicals characteristics of vegetative organs of Catalpa bignonioides Walt., level of damage of leaves and their pathological changes were studied.